Cbl downregulation increases RBP4 expression in adipocytes of female mice. Issue 1 (January 2018) - Ameen, Gulizar Issa; Mora, Silvia
Abstract : Obesity leads to adipose tissue dysfunction, insulin resistance and diabetes. Adipose tissue produces adipokines that contribute to regulate insulin sensitivity. In turn, insulin stimulates the production and release of some adipokines. Casitas-b-lymphoma proteins (c-Cbl, Cbl-b and Cbl3) are intracellular adaptor signalling proteins that are rapidly phosphorylated by activation of tyrosine kinase receptors. c-Cbl is rapidly phosphorylated by insulin in adipocytes. Here, we tested the hypothesis that Cbl signalling regulates adipokine expression in adipose tissue. We determined the adipokine profile of WAT of Cbl−/− and Cbl+/+ mice in the C57BL6 background. Female Cbl−/− mice exhibited altered expression of adiponectin, leptin and RBP4 in visceral adipose tissue, while no significant changes were seen in male mice. TNFα and IL6 levels were unaffected by Cbl depletion. RBP4 expression was unchanged in liver. Adipose tissue of Cbl−/− animals showed increased basal activation of extracellular regulated kinases (ERK1/2) compared to Cbl+/+. c-Cbl knockdown in 3T3L1 adipocytes also increased basal ERK phosphorylation and RBP4 expression. Inhibition of ERK1/2 phosphorylation in Cbl-depleted 3T3L1 adipocytes or in adipose tissue explants of Cbl−/− mice reduced RBP4 mRNA. 17β-Estradiol increased RBP4 mRNA in adipocytes. Cbl depletion did not change ER expression but increased phosphorylation of ERα at S118, a target site for ERK1/2. ERK1/2 inhibition reduced phosphoER and RBP4 levels. These findings suggest that Cbl contributes to regulate RBP4 expression in adipose of female mice through ERK1/2-mediated activation of ERα. Since Cbl signalling is compromised in diabetes, these data highlight a novel mechanism that upregulates RBP4 locally.